Lithuanian Clergy as the Fosterer of National Self-Consciousness and Economical Self-Expression - Pruskus, Valdas (Problemos, 1995)
The attitude of Lithuanian Catholic clergy towards the socio-econometric problems in the end of 19th century in Lithuania is considered in the article. The clergy, it is said, was wise enough to notice the threat of foreign economic influence upon identity of Lithuanians. Enhancement of the economical independence was viewed by the clergy as the way of acquisition of political independence of Lithuania.